1986
DOI: 10.1148/radiology.161.2.3763920
|View full text |Cite
|
Sign up to set email alerts
|

Dedifferentiated chondrosarcoma: radiographic features.

Abstract: Dedifferentiated chondrosarcomas, unlike ordinary chondrosarcomas, are highly aggressive tumors that frequently metastasize. The lesion is characterized by a lytic intraosseous or extraosseous soft-tissue mass that is devoid of the calcifications that are usually associated with a chondroid tumor. We describe the radiographic and pathologic features of five cases involving dedifferentiated chondrosarcoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
1

Year Published

1994
1994
2017
2017

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 0 publications
2
11
1
Order By: Relevance
“…10 However, in our series, just Ͼ50% of lesions had the radiographic aspect of a dedifferentiated chondrosarcoma. This finding is consistent with previous reports.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…10 However, in our series, just Ͼ50% of lesions had the radiographic aspect of a dedifferentiated chondrosarcoma. This finding is consistent with previous reports.…”
Section: Discussioncontrasting
confidence: 52%
“…3,4 Although there are numerous single patients and small series of patients with dedifferentiated chondrosarcomas reported in the literature, [5][6][7][8][9][10][11][12] only a very few large series have been published. 3,4,13,14 Therefore, many uncertainties remain about prognostic factors for patients with this lesion.…”
mentioning
confidence: 99%
“…This group was first described by Dahlin and Beabout [11]. It includes 1%-2% of all primary bone tumours [22]. From the time of diagnosis the mean survival period is approximately 2 years.…”
Section: Introductionmentioning
confidence: 99%
“…Histologically, DDCS consists of two distinguishable components: the chondroid component and the dedifferentiated component. The chondroid component can be an enchondroma or chondrosarcoma (CS) of any grade [9,11,22,23,24,25,26,30,32,33]. Mercuri et al [25] reported a rather high proportion of enchondromas (10/74) coexisting with the dedifferentiated component.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation